Impact of physical activity on all-cause mortality in European patients with atrial fibrillation: a report from the ESC-EHRA EORP AF General Long-Term Registry. (25th November 2020) - Vitolo, M; Proietti, M; Harrison, S; Kalarus, Z; Tavazzi, L; Potpara, T; Lane, D.A; Boriani, G; Lip, G.Y.H
Abstract: Background: Physical activity (PA) may have a beneficial contribution for outcomes in patients with atrial fibrillation (AF). Purpose: We aimed to evaluate the impact of self-reported PA in a large contemporary cohort of European AF patients on the risk of all-cause mortality. Methods: We analyzed patients enrolled in the ESC-EHRA EORP-AF General Long-Term Registry. Self-reported PA was categorized, on the basis of reported time spent exercising, as follows: i) No PA; ii) Occasional PA; iii) Regular PA; iv) Intense PA. The primary outcome was all-cause death. Results: Over 11096, a total of 8699 (78.4%) patients (mean age (SD) 69.1 (11.5); 40.7% female) had available data about PA and follow-up observation and were included in the analysis. Of these, 3703 (42.6%) reported no PA, 2829 (32.5%) occasional PA, 1824 (21.0%) regular PA, with only 343 (3.9%) reporting intense PA. With the 4 increasing PA categories, mean age, proportion of female patients, CHA2DS2-VASc and HAS-BLED scores were progressively lower (all p<0.001). Use of vitamin K antagonist (VKA) declined across the classes of PA (53.1% vs. 52.2% vs. 44.5% vs. 33.9%, p<0.001), while use of non-VKA OACs (NOACs) conversely increased. During a mean (SD) 680.6 (171.5) days of follow-up, there were a total of 848 (9.7%) all-cause death events. Based on Kaplan-Meier analysis, there was a progressively lower cumulative risk for all-cause death according to PA categories [Figure]. A multivariable Cox regression analysis, adjusting for CHA2DS2-VASc score, use of OAC at baseline and type of AF, found a lower risk of all-cause death associated with increasing levels of PA (Hazard ratio [HR]: 0.69, 95% confidence interval [CI]: 0.59–0.81 for occasional PA, HR: 0.45, 95% CI: 0.35–0.58 for regular PA, HR: 0.41, 95% CI: 0.23–0.76 for intense PA, when compared to no PA). In a sensitivity analysis, a regular-intense PA was inversely associated with occurrence of cardiovascular (CV) death, after multivariable adjustments for comorbidities (HR: 0.54, 95% CI: 0.37–0.77). Conclusions: In a large contemporary cohort of European AF patients, self-reported PA was found to be inversely associated with all-cause death and CV death. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Since the start of EORP, several companies have supported the programme with unrestricted grants